2018
DOI: 10.1007/978-3-319-95993-1_11
|View full text |Cite
|
Sign up to set email alerts
|

Evidentialism and Moral Encroachment

Abstract: Moral encroachment holds that the epistemic justification of a belief can be affected by moral factors. If the belief might wrong a person or group more evidence is required to justify the belief. Moral encroachment thereby opposes evidentialism, and kindred views, which holds that epistemic justification is determined solely by factors pertaining to evidence and truth. In this essay I explain how beliefs such as 'that woman is probably an administrative assistant'-based on the evidence that most women employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(43 citation statements)
references
References 65 publications
0
39
0
4
Order By: Relevance
“…Fritz and Jackson (n.d.) argue that some theorists—specifically, advocates of Radical Moral Encroachment—who don't advocate moral encroachment on credences are nevertheless committed to it. Finally, several authors who deny encroachment on credences (Bolinger, 2018; Fritz, 2019; Gardiner, 2018; Munton, 2019) have argued that in many of the cases used to motivate moral encroachment, the agent's evidence does not even license rational high credence by ordinary epistemic standards.…”
Section: All In the Family? The Relationship Between Pragmatic And Momentioning
confidence: 99%
See 1 more Smart Citation
“…Fritz and Jackson (n.d.) argue that some theorists—specifically, advocates of Radical Moral Encroachment—who don't advocate moral encroachment on credences are nevertheless committed to it. Finally, several authors who deny encroachment on credences (Bolinger, 2018; Fritz, 2019; Gardiner, 2018; Munton, 2019) have argued that in many of the cases used to motivate moral encroachment, the agent's evidence does not even license rational high credence by ordinary epistemic standards.…”
Section: All In the Family? The Relationship Between Pragmatic And Momentioning
confidence: 99%
“…Gardiner (2018) characterizes moral encroachment slightly more narrowly, as the thesis that “moral features of a belief can affect whether the belief is epistemically justified”, which is basically equivalent to the gloss in Basu (2019a) “the epistemic justification of our beliefs can be determined, in part, by the moral demands of our situation, i.e., the moral stakes.” Moss (2018a)'s characterization is slightly broader: “the moral encroachment thesis is equivalent with the claim that the epistemic status of an opinion can depend on its moral features.”…”
mentioning
confidence: 99%
“…Cohen & Rozin, 2001;Keller, 2004;McManus, Kleiman-Weiner, & Young, 2020;Stroud, 2006). Alternatively, as some philosophers have argued, making race-or sex-based inferences may fail to treat minorities with due respect, even when they are based on evidence (e.g., Basu, 2019; but see Gardiner, 2018). Some work has shown that people will disregard certain kinds of evidence when making decisions, such as when it would lead them to convict someone of a crime based on statistical evidence (Nesson, 1985;Wells, 1992) or when relevant statistical evidence is caused by race-based inequality or discrimination (Tetlock et al, 2000).…”
Section: The Case For Moral Encroachment On Belief Evaluationmentioning
confidence: 99%
“…Gardiner () notes this point as a challenge to any account of moral encroachment. She says, “[m]oral encroachment risks making epistemic justification contingent on myriad complex social factors that are intuitively irrelevant to epistemic justification.” But here's the rub, beliefs are central to our social relationships with one another, and if we understand radical moral encroachment as a way of making good on the demand to stay woke, then the myriad of complex social factors are features of our epistemic environment that we ought be attending it.…”
mentioning
confidence: 99%